African swine fever virus assembles a single membrane derived from rupture of the endoplasmic reticulum. (24th July 2015) - Suarez, Cristina; Andres, German; Kolovou, Androniki; Hoppe, Simone; Salas, Maria L.; Walther, Paul; Krijnse Locker, Jacomine
Summary Collective evidence argues that two members of the nucleocytoplasmic large DNA viruses (NCLDVs) acquire their membrane from open membrane intermediates, postulated to be derived from membrane rupture. We now study membrane acquisition of the NCLDV African swine fever virus. By electron tomography (ET), the virion assembles a single bilayer, derived from open membrane precursors that collect as ribbons in the cytoplasm. Biochemically, lumenal endoplasmic reticulum (ER) proteins are released into the cytosol, arguing that the open intermediates are ruptured ER membranes. ET shows that viral capsid assembles on the convex side of the open viral membrane to shape it into an icosahedron. The viral capsid is composed of tiny spikes with a diameter of ∼5 nm, connected to the membrane by a 6 nm wide structure displaying thin striations, as observed by several complementary electron microscopy imaging methods. Immature particles display an opening that closes after uptake of the viral genome and core proteins, followed by the formation of the mature virion. Together with our previous data, this study shows a common principle of NCLDVs to build a single internal envelope from open membrane intermediates. Our data now provide biochemical evidence that these open intermediates result from rupture of a cellular membrane, the ER.